2004
DOI: 10.1139/h04-010
|View full text |Cite
|
Sign up to set email alerts
|

Do Gender Differences in Running Performance Disappear With Distance?

Abstract: It has been suggested that gender differences in running should disappear as distances increase, particularly past the marathon. This suggestion is primarily based on differences in fuel utilization, muscle damage following exercise, relative improvements in performance over the past decades, and on the analysis of marathon vs. ultramarathon performances of men and women. We reasoned that the best comparison of the potential of a human is by the use of world best times, which should be reasonable indicators of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
141
4
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(164 citation statements)
references
References 13 publications
12
141
4
3
Order By: Relevance
“…In the study of Coast et al (6) relating to running distances between 100 m and 200 km, the sex difference accounted to 12.4%. The existing sex gaps in running performance can partly be attributed to physiological sex differences such as the lower skeletal muscle mass and the lower cardiac output in women compared with men (5,39).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In the study of Coast et al (6) relating to running distances between 100 m and 200 km, the sex difference accounted to 12.4%. The existing sex gaps in running performance can partly be attributed to physiological sex differences such as the lower skeletal muscle mass and the lower cardiac output in women compared with men (5,39).…”
Section: Discussionmentioning
confidence: 90%
“…However, the sex difference in performance was only ;20% for the annual top 10 runners over the years (11). In contrast, in the study of Coast et al (6) investigating athletes covering distances between 100 m and 200 km, the sex difference accounted to 12.4%.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Although some authors have questioned whether the gap in gender difference in endurance performance could be closed (Bam, Noakes, Juritz, & Dennis, 1997;Coast, Blevins, & Wilson, 2004;Whipp, & Ward 1992), more recent studies could not confirm this assumption showing that the gender difference in both endurance performance (Cheuvront, Carter, DeRuisseau, & Moffart, 2005;Sparling, O'Donnell, & Snow, 1998) and anaerobic sprints (Seiler, De Koning, & Foster, 2007) is no longer diminishing. Coast et al (2004) for example analysed the gender difference in running performances at distances from 100 m to 200 km. They found a gender difference in average speed of 12.4% and also showed that longer running distances were associated with greater gender differences.…”
Section: Introductionmentioning
confidence: 99%
“…There was a significant slope to the speed difference across distances where longer distances were associated with greater differences [31]. In 24-hour ultramarathons held between 1977 and 2012, the sex differences were ~5% for all women and men, ~13% for the annual fastest finishers, ~13% for the top ten and ~12% for the top 100 finishers [30].…”
Section: Performance In Women and Men And Sex Difference In Performancementioning
confidence: 94%